Chemical Characteristics and Physical Properties of Functional Snacks Enriched with Powdered Tomato - Wójtowicz Agnieszka; Zalewska-Korona Marta; Jabłońska-Ryś Ewa; Skalicka-Woźniak Krystyna; Oniszczuk Anna (Polish Journal of Food and Nutrition Sciences)
The paper discusses the influence of the addition of freeze-dried tomatoes on the chemical composition and selected physical properties of extruded corn snacks. Corn grits were replaced with dried tomatoes in the amount from 5 to 30% of corn mass. The total lycopene and phenolic content, the scavenging ability and the ferric reducing antioxidant power were determined along with the content of neochlorogenic, chlorogenic, p-coumaric acids and rutin. Also evaluated were selected physical properties, colour and the sensory profile of corn snacks enriched with tomatoes. A greater tomato addition increased the volume of bioactive compounds, especially the total phenolic content. Snacks enriched with tomato exhibited a lower expansion ratio, water absorption and solubility indices, lightness and sensory characteristics but higher density, hardness and redness than corn snacks. Powdered tomato seems to be a functional additive with the high content of biologically-active compounds, and the enriched snacks displayed good physical properties if the tomato level did not exceed 20%. A higher amount of the additive significantly lowered the expansion as well as increased the hardness of snacks. Still, the corn products with 25 and 30% of powdered tomato were more valuable due to their much higher level of bioactive components compared with the regular corn snacks.